Bullying: uma das faces do preconceito homofóbico entre jovens no contexto escolar - Souza, Jackeline Maria de (2013)
Among the various ways to understand the school violence, currently has been highlighting a specific form called bullying. Conceptually, the bullying is defined as a repetitive violence, physical or psychological, may be direct or indirect, that is established in an unequal relationship of power between pairs, producing negative consequences to the target. In the present study is an approximation of this phenomenon with homophobia and bullying one of the forms of manifestation of that prejudice within schools. Given this, the present study had as general objective to analyze the bullying on young people from public schools of Aracaju, as well as the relationship of their demonstration with homophobia. Attended 808 young with an average age of 14.9 years (SD = 1.98), from 9 State schools of the city of Aracaju-SE. the procedure of data collection occurred in schools, in a collective way and during a period of class assigned by the teacher. The collection was divided into two steps: (1) delivery of Term of free and Clarified Consent (TFCC) to students and explanation of the research; (2) the next day, returned to collect the TFCC signed by responsible and application of the questionnaire. Among the participants, the majority were female (57%), Browns (52%) and claimed to belong to any religion (93%). The instruments used were a questionnaire of bullying, homophobia and the general health questionnaire (GHQ). For data analysis was descriptive and inferential statistics. The results indicated that, among the participants, 32% self-identified as targets of bullying, 12% authors, 22% and 34% authors targets only witnesses. Homophobia has been described between the targets as responsible for 9% of the cases of bullying only among boys this percentage represented 22% of the cases; and 2% among girls. It was observed that the Group of authors of bullying, homophobia, scores are more differentiating statistically (p < 0.05) of the target groups. In addition, it is noticed that bullying interferes with the psychological well-being of the subjects, being the target groups-authors and targets participants with lower well-being, differentiating statistically.